Manufacturing method of composite material part
By applying the anti -moisturizing combination layer of the fiber structure of the ceramic base composite material component, the problem of the surface smoothness and shape tolerance of the parts in the existing technology is solved, and the simpler and economic component preparation process is achieved.
Patent Information
- Application Number
- CN202380044684.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-21
AI Technical Summary
When the existing melt impregnation technology forms ceramic matrix composite components, it is difficult to ensure the surface finish and shape tolerance of the components, resulting in complicated and increased subsequent processing steps.
Before the impregnation step, the component of the fibrous structure is prepared by applying a layer of an antiwetting composition containing 20% to 80% of an antiwetting agent powder of the impregnating composition with a median particle size distribution of 1.0 μm to 50μm.
By applying a layer of anti-wetting composition, it is possible to prevent the impregnating composition from wetting the outer surface of the fiber structure, reduce surface condition, simplify the preparation process of the part, and improve surface finish.
Smart Images

Figure HDA0005166984130000011 
Figure HDA0005166984130000021 
Figure HDA0005166984130000022
Abstract
Description
Technical Field
[0001] The present invention relates to the field of manufacturing composite material parts and more particularly to the field of parts formed by a process of infusion of a composition in the molten state. Prior art
[0002] Ceramic matrix composite (CMC) materials are known for their good mechanical properties, which make them suitable for constituting structural elements and maintaining these properties at high temperatures, making them a viable alternative to traditional metal parts. Their reduced mass compared to metal equivalents makes them the preferred component to solve the problems of improving efficiency and reducing engine polluting emissions in the aviation sector.
[0003] CMC material parts may include continuous fiber reinforcement in the form of a woven fabric, which is densified by a ceramic matrix. The fiber reinforcement thus includes long continuous fibers, the orientation of which may be adapted to the main stress directions on the part during its use. The preform used to form the fiber reinforcement is a weaving of the continuous fibers to the dimensions of the part using a suitable loom.
[0004] In addition, it is known to obtain the matrix of these parts from CMC materials by melt impregnation technology. According to this technology, a molten composition based on silicon in the molten state, for example, can be introduced into the pores of a fiber structure containing silicon carbide particles to form a ceramic matrix of a densified fiber structure. In this technology, it is desired that the molten composition is uniformly and completely impregnated into the pores of the fiber structure, so that the obtained parts have a minimum residual porosity and therefore have optimized mechanical properties. Usually, the impregnation of the fiber preform with molten silicon is produced by immersing a small part of the fiber preform in a liquid silicon bath by capillary action.
[0005] However, some melt infusion techniques do not give completely satisfactory results, since the areas of the preform in contact with the molten silicon bath may present a surface finish that does not conform to the shape tolerances admissible for the part. Furthermore, the deteriorated surface condition makes any subsequent processing steps of the infused part more difficult, such as the deposition of environmental barriers that typically coat such parts.
[0006] To solve this problem, several solutions have been proposed. For example, a sacrificial excess length can be provided and removed after impregnation to obtain a part with an acceptable surface condition. The first solution complicates the manufacturing method by imposing an additional step and causes material losses that, multiplied by the number of parts, can mean significant costs.
[0007] Another advanced solution is to machine the components whose surface condition has been deteriorated by impregnation after impregnation in order to restore them to an acceptable condition and meet form tolerances. This machining can be done, for example, by sandblasting. However, such machining is undesirable because, in addition to being expensive and time consuming, it can also result in localized degradation of the component, which can lead to premature wear of the component or result in mechanical properties that are lower than expected.
[0008] Another method to overcome the above problems is not to dip the preform by immersing it directly into the molten silicon bath, but to insert a drain tube between the molten silicon bath and the preform.
[0009] However, it is observed that this solution is not entirely satisfactory, at least because it does not completely solve the problem of the deterioration of the surface condition of the parts thus obtained.
[0010] Therefore, there is still a need for a solution that allows the impregnation of a preform with molten silicon while avoiding one or more of the disadvantages described for the solutions of the prior art. Summary of the invention
[0011] In order to meet this demand, the present invention provides a method for manufacturing a ceramic matrix composite component, which at least comprises:
[0012] - a step of impregnating the fibrous structure by immersing a portion of the fibrous structure in a bath of an impregnation composition comprising at least silicon in the molten state,
[0013] The method is characterized in that, before the impregnation step, it includes a step of preparing the part of the fiber structure intended to be immersed in a bath of an impregnation composition, the preparation step including applying at least a layer of an anti-wetting composition, the anti-wetting composition comprising 20% to 80% by mass of an anti-wetting agent powder of the impregnation composition, the median value of the particle size distribution of the anti-wetting agent powder being 1.0 μm to 50 μm.
[0014] The treatment of immersing the part of the fiber structure in a bath of the impregnating composition containing the anti-wetting composition makes it possible to prevent the impregnating composition from wetting the outer surface of the fiber structure and degrading its surface condition.
[0015] However, it is noteworthy that the anti-wetting composition does not impair the capillarity necessary for good impregnation of the preform by the impregnation composition.
[0016] Furthermore, the anti-wetting composition also does not reduce the thermomechanical properties of the impregnated preform, and can therefore very advantageously simplify the process for producing components made of composite materials with a ceramic matrix.
[0017] In the present application, the term "anti-wetting composition" or "anti-wetting agent" must be understood in the usual sense of physical wetting between a surface and a liquid, the surface being the surface of the fiber structure and the liquid being the impregnation composition. Wetting can be measured by the contact angle, which is usually defined, i.e. the tangent to the liquid at the point of the air / liquid / surface interface. The smaller the contact angle, the better the wettability.
[0018] As can be seen above, and since anti-wetting agents are intended to reduce the wetting of a surface by a liquid, within the meaning of the present invention, an "anti-wetting" agent is defined by its ability to increase the contact angle, which is the angle between the impregnating composition and the surface of the fibrous structure.
[0019] In one embodiment, the anti-wetting agent may be selected from aluminum oxide, boron nitride, yttrium oxide, silicon dioxide, silicon nitride or a mixture of several compounds selected from the previous list. Preferably, the anti-wetting agent is boron nitride or yttrium oxide, or even yttrium oxide.
[0020] In one embodiment, application of the anti-wetting composition may be accomplished by spraying, by dipping the fiber structure into a bath of the anti-wetting composition, or by application with a brush.
[0021] As indicated, the step of applying the anti-wetting composition is carried out on the portion of the fibrous structure intended to be immersed in the bath of the impregnation composition.
[0022] In one embodiment, the portion of the fiber structure to be impregnated may be defined as a strip having a width between 1 mm and 10 mm from one end of the fiber structure.
[0023] The inventors have noted that this choice of the portion of the fibrous structure in contact with the impregnation bath ensures that the surface of the fibrous structure is immersed in the bath of impregnation composition, so as to achieve a good capillary rise of the impregnation composition throughout the fibrous structure.
[0024] In one embodiment, each step of applying the anti-wetting composition may be followed by a drying step.
[0025] For example, such a drying step can be carried out in air or in a furnace.
[0026] For example, the drying step may last from 5 minutes to 30 minutes.
[0027] In one embodiment, the preparing step comprises one or more consecutive steps of applying a layer of the anti-wetting composition and a drying step.
[0028] The application of multiple layers of the anti-wetting composition ensures that the entire area of interest, ie the portion of the fiber structure immersed in the bath of the impregnation composition, is covered by at least one layer of the anti-wetting composition.
[0029] In fact, the thickness of the anti-wetting composition applied has little influence on the technical effect obtained, but preferably, the entire portion of the fibrous structure immersed in the bath of the impregnating composition is covered with at least one layer of the anti-wetting composition.
[0030] In one embodiment, the anti-wetting composition comprises an anti-wetting agent powder in an amount between 20% and 40% by mass of the alloy.
[0031] In fact, the inventors have noticed that reducing the mass content of anti-wetting agent makes it possible to obtain a good compromise between the effect obtained and the price of the anti-wetting composition.
[0032] In one embodiment, the anti-wetting composition may include a powder of a solvated anti-wetting agent. For example, the solvent for the anti-wetting composition may be water or an alcohol, such as ethanol.
[0033] In one embodiment, the median particle size distribution of the anti-wetting agent powder is between 1.0 μm and 20 μm.
[0034] The median particle size distribution of a powder is understood in the present application to be the number median, also called D50, around which the diameters of the powder particles extend.
[0035] In one embodiment, the particle size distribution can be measured by statistical counting, for example, by images obtained by scanning electron microscopy. This method is for reference only, and any other method that allows statistical counting and determination of particle size distribution can be used for the purpose of the present invention.
[0036] The inventors have noted that the proposed particle size distribution makes it possible to further improve the anti-wetting properties of the anti-wetting composition.
[0037] In one embodiment, the anti-wetting composition may be removed between the step of applying the anti-wetting composition and the step of impregnating.
[0038] In fact, the anti-wetting composition does not require modification of the surface finish of the preform in order to obtain an improved surface condition compared to prior art materials.
[0039] In one embodiment, unlike prior art solutions which propose to physically modify the surface condition of the preform prior to molten silicon impregnation, for example by forming a smoother layer on the surface of the preform, it is noted that the impregnation composition does not change the surface condition of the preform.
[0040] The application of the anti-wetting composition only changes the wetting properties of the fiber preform.
[0041] Without wishing to be bound by theory, the inventors have observed that it is these changes in wetting properties that lead to the improved surface conditions observed as a result of the process of the invention.In one embodiment, the impregnation of the preform may be preceded by an impregnation step with a slurry containing ceramic and / or carbon particles.
[0042] Such slurry impregnation prior to impregnation with molten silicon is well known to those skilled in the art and allows the formation of a ceramic matrix.
[0043] In one embodiment, the impregnation composition may be selected from pure silicon in a molten state or a silicon alloy in a molten state.
[0044] In one embodiment, the fiber structure is a fiber preform of a turbine engine component.
[0045] In one embodiment, such a turbine engine component may be, for example, a fiber preform of a stationary blade or a movable blade, a fiber preform of an annular sector or a combustion chamber of a turbine engine.
[0046] In one embodiment, the portion of the fibrous structure immersed in the bath of the impregnation composition is a portion of a fibrous structure intended to form the root of a turbine engine blade.
[0047] The inventors have observed that the method of the invention is particularly suitable for turbine engine blades, and more so when the portion intended to form the root of the blade is immersed in the impregnation composition.
[0048] In fact, the method of the invention makes it possible to obtain the above-mentioned effects for parts which can most likely be manufactured by infusion in the molten state.
[0049] Furthermore, the root of a turbine engine blade is subject to strict tolerances in terms of shape and surface condition, and the method of the invention makes it possible to obtain such strict tolerances, thus making it possible to obtain a CMC turbine engine blade in a simpler and more economical way than the methods of the prior art. In fact, it makes it possible to avoid providing sacrificial excess material and to avoid machining steps after impregnation in order to restore the surface condition.
[0050] BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 A device capable of impregnating a preform by the method according to the invention is schematically represented.
[0052] Figure 2 is a photograph of a part obtained by the method according to the invention.
[0053] Figure 3 is a photograph of a comparative part obtained by a method other than the present invention. DETAILED DESCRIPTION
[0054] The present invention will now be described by way of the accompanying drawings, which are shown for descriptive purposes to illustrate certain embodiments of the invention and which should not be construed as limiting the invention.
[0055] Figure 1 A cross-sectional view of a furnace 1 is shown, which can be used in the impregnation step of the method for producing a CMC part according to the invention. The furnace 1 comprises a gastight chamber 2, inside which there is a crucible 4 having an internal volume containing an impregnation composition 6, and a support tool 100 comprising a plurality of individual supports 300, each of which is loaded with a fiber structure, here very schematically a porous turbine engine blade preform 400, the plurality of individual supports 300 being held in a single cluster 100, the cluster 100 also comprising a holding arm 240.
[0056] The crucible 4 may be made of a ceramic material. The impregnation composition 6 may be, for example, silicon or a silicon alloy. Here, the furnace 1 is provided with a resistance heating system 10, for example comprising a graphite rod. The heating system 10 is arranged around the crucible 4 and the preform 400 in the chamber 2 of the furnace 1. The heating system also comprises a generator 16 in a known manner to provide power for the heating system. The furnace 1 may also be provided with a vacuum pump 18 in fluid communication with the interior of the chamber 2 to perform a vacuum impregnation process. Note that another type of furnace than that shown may be used, in particular the furnace may comprise an induction heating system instead of a resistance system.
[0057] The furnace 1 comprises means for measuring the mass of the preform 400, here corresponding to a loadcell type balance 20. In this example, the balance 20 is located outside the chamber 2 of the furnace 1, above the chamber 2. Of course, other mass measuring means may be used without departing from the framework of the invention.
[0058] The furnace 1 also comprises a moving device, which here comprises a cylinder 24 with a rod 26, on which the crucible 4 is mounted. In this example, the cylinder 24 is located outside the chamber 2 of the furnace 1, below the chamber 2. In this way, the cylinder 20 enables the crucible 4 to be moved in a vertical translational movement inside the chamber 2 of the furnace 1, in particular towards the porous preform 400. Thus, the crucible 4 can be moved in a vertical translational movement inside the chamber 2. In a variant (not shown), the crucible can be fixedly mounted in the furnace and the preform can be moved in a vertical translational movement.
[0059] In the example shown, the furnace 1 further comprises a control system 28 for controlling the relative position between the preforms and the crucible, which is configured to control the cylinders 24 according to the development of the mass of the preforms 400 measured by the balance 20. The balance 20 supports all the preforms 400 by means of a holding arm 240. The control system 28 can be, for example, an automatic machine or a computer equipped with an input / output acquisition card. The control system 28 can receive an electrical signal from the balance 20 as an input and send a control signal to the cylinders 24 as an output.
[0060] The impregnation of the porous preform 400 is carried out by bringing the preform 400 into contact with the surface 6a of the impregnation composition 6, which may be, for example, silicon or a silicon alloy, and the impregnation composition 6 impregnates the pores of the preform by capillary action. When in contact, the lower part of the preform 400 is directly immersed in the bath of the impregnation composition 6, which is then transported into the preform 400 by capillary action. The contact of the preform with the impregnation composition 6 and thus the impregnation of the preform with the impregnation composition 6 are controlled by controlling the cylinder 24. When the balance 20 measures a predetermined mass gain corresponding to the desired densification level of the preform 400, the impregnation of the preform 400 with the impregnation composition 6 is terminated. A part made of a CMC material including a fiber reinforcement densified by a matrix is then obtained.
[0061] To implement the method according to the invention, the lower part of the preform 400 is covered with an anti-wetting composition, prior to the impregnation just described.
[0062] In order to characterize the effect of the preparation steps of the method according to the invention, two turbine engine blade preforms were impregnated with molten silicon, one according to the method according to the invention and the other according to a method other than the method according to the invention (same as the method according to the invention in all respects except that the second preform did not undergo a preparation step, that is, it was not covered with an anti-wetting composition).
[0063] For this example, the anti-moisture composition is a composition containing 30% by mass of boron nitride powder having a median particle size of 10 μm, and the remainder of the composition is a mixture of acetone, butane, propane, and methyl ethyl ketone used as a solvent.
[0064] The anti-wetting composition is deposited on the root area of the blade, which is then immersed in a bath of molten silicon.
[0065] The two parts were then visually compared.
[0066] Figure 2 and Figure 3 According to the method of the present invention ( Figure 2 ) and methods other than the present invention ( Figure 3 ) Photograph of the two parts impregnated.
[0067] The box in the photo marks the area of the part that is immersed in the molten silicon bath.
[0068] By comparison Figure 2 and Figure 3 It can be noted that implementation of the invention makes it possible to obtain parts having a surface state that is much smoother than that of parts impregnated according to a method other than the invention.
[0069] In order to ensure that the presence of the anti-wetting composition did not impair proper impregnation of the part with the molten silicon, the density of the two parts was compared and was equal in both cases.
[0070] This example therefore shows that carrying out the process of the invention makes it possible to obtain parts having a greatly improved surface condition, without compromising good impregnation of the parts with the impregnation composition.
Claims
1. A method for manufacturing a ceramic matrix composite component, comprising at least: - a step of impregnating the fibrous structure (400) by immersing a portion of the fibrous structure (400) in a bath (6) of an impregnation composition, said impregnation composition comprising at least silicon in the molten state, The method is characterized in that it comprises, before the impregnation step, a step of preparing the portion of the fiber structure to be immersed in a bath of an impregnation composition, the preparation step comprising applying at least a layer of an anti-wetting composition, the anti-wetting composition comprising 20% to 80% by mass of an anti-wetting agent powder of the impregnation composition, the median particle size distribution of the anti-wetting agent powder being between 1.0 μm and 50 μm.
2. The manufacturing method according to claim 1, wherein: The anti-wetting agent is selected from aluminum oxide, boron nitride, yttrium oxide, silicon dioxide, silicon nitride or a mixture of the aforementioned compounds.
3. The manufacturing method according to claim 1 or 2, wherein: The preparation step includes one or more consecutive steps of applying a layer of an anti-wetting composition and a drying step.
4. The manufacturing method according to any one of claims 1 to 3, wherein: The application of the anti-wetting composition is carried out by spraying, by dipping the fiber structure into a bath of the anti-wetting composition, or by using a brush.
5. The manufacturing method according to any one of claims 1 to 4, wherein: The anti-wetting composition comprises between 20 mass % and 40 mass % of an anti-wetting agent powder of the alloy.
6. The manufacturing method according to any one of claims 1 to 5, wherein: The median particle size of the anti-moisture agent powder is distributed between 1.0 μm and 20 μm.
7. The manufacturing method according to any one of claims 1 to 6, wherein: The fiber structure (400) is a fiber preform of a turbine engine component.
8. The manufacturing method according to any one of claims 1 to 7, wherein: The fiber structure (400) is a fiber preform of a fixed blade or a movable blade of a turbine engine, a fiber preform of an annular sector or a combustion chamber.
9. The manufacturing method according to claim 8, wherein: The portion of the fiber structure (400) immersed in the bath (6) of the impregnation composition is a portion of a fiber structure intended to form the root of a turbine engine blade.